HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN KEJADIAN PRE EKLAMPSIA PADA IBU HAMIL DI RUMAH SAKIT BHAYANGKARA: HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN KEJADIAN PRE EKLAMPSIA PADA IBU HAMIL DI RUMAH SAKIT BHAYANGKARA - Palupi Pusporini; Widia Shofa Ilmiah; Rosyidah Alfitri (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: Pre-eclampsia is one of the causes of death in mothers and babies. One of the factors related to the occurrence of pre-eclampsia is obesity. Obesity can be identified using the Body Mass Index (BMI). This study aims to analyze the relationship between Body Mass Index (BMI) and the incidence of pre-eclampsia in pregnant women at Bhayangkara Hospital. Method: This type of research is observational and uses a cross-sectional research design. The total sample was 40 pregnant women determined using the total sampling technique. The research instrument used an observation sheet. Data were analyzed using the Spearman rank correlation test with a significance value <α=0.05. Results: The study showed that most of the body mass index was in the overweight or obese category, amounting to 32 respondents (80%). The incidence of pre-eclampsia in almost all respondents with severe pre-eclampsia was 35 respondents (87.5%). The Spearman rank test results showed a P-value = 0.000 < α 0.05, meaning there is a relationship between body mass index and the incidence of pre-eclampsia. Conclusion: There is a relationship between body mass index and the incidence of pre-eclampsia. The suggestion is the need for health workers to make innovations related to preventing pre-eclampsia.